2019
DOI: 10.1167/iovs.18-25453
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography in Papilledema Compared With Pseudopapilledema

Abstract: PurposeThe purpose of this study is to evaluate differences in optical coherence tomography angiography (OCT-A) findings between patients with papilledema and pseudopapilledema.MethodsIn this prospective, comparative study, 41 eyes of 21 subjects with papilledema, 27 eyes of 15 subjects with pseudopapilledema, and 44 eyes of 44 healthy normal subjects were included and were imaged using OCT-A. In addition to peripapillary total vasculature maps obtained with commercial vessel density mapping, major vessel remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 25 publications
(49 reference statements)
1
44
1
Order By: Relevance
“…26 Furthermore, Fard et al demonstrated that OCT-A in papilloedema demonstrated increased whole image density and nasal peripapillary density compared to discs with pseudopapilloedema. 59 This was particularly obvious in papilloedema grades 1 and 2. 59 In grade 3 or 4 papilloedema, the peripapillary capillary density was reduced and was not very useful to differentiate between grade 3 or 4 papilloedema from pseudo-papilloedema.…”
Section: Disc Swelling Due To Raised Intracranial Pressurementioning
confidence: 97%
“…26 Furthermore, Fard et al demonstrated that OCT-A in papilloedema demonstrated increased whole image density and nasal peripapillary density compared to discs with pseudopapilloedema. 59 This was particularly obvious in papilloedema grades 1 and 2. 59 In grade 3 or 4 papilloedema, the peripapillary capillary density was reduced and was not very useful to differentiate between grade 3 or 4 papilloedema from pseudo-papilloedema.…”
Section: Disc Swelling Due To Raised Intracranial Pressurementioning
confidence: 97%
“…Summarizing our findings, in HAE patients, we might assume that a subclinical edema formation increases the thickness of the parafoveal area and leads to a "relative" reduction of the vascular network by compressing the existing capillaries [27,28]. The significant reduction in vessel density values that was detected in HAE cohort looks like the low vessel density documented in patients with papilledema and pseudopapilledema in whom hypothetically the apparent reduced density of vessels on OCT-A might be due to slow flow resulting from compression/stasis [28,29]. In this view, in C1INH deficiency-HAE the endothelial barrier failure with enhanced vascular permeability can likely involve tissues and organs at the site of attacks [3].…”
Section: Resultsmentioning
confidence: 93%
“…Further investigations including a larger HAE cohort might lead to an improvement of the analysis by comparing among subgroups of patients (e.g., between patients currently taking androgens and having ever taken androgens, as well as patients experiencing treated vs. untreated attacks). In addition, future studies on structural analysis of the retina are certainly awaited [29,31].…”
Section: Resultsmentioning
confidence: 99%
“…and two studies were related to the optic disc edema. [19,20] All of them are small sampled size (~6-41 eyes) or (~ 5-30 patients) in NA-AION and (˜25-44 eyes) or (˜12-22 patients) in papilledema, and some of them are retrospective and without a control group. Mean age, time of diagnosis (acute ou non-acute), and gender had wide variability.…”
Section: Resultsmentioning
confidence: 99%
“…(2) possible dropout in the chronic stages or very severe edema causing compression or undetectable by the sluggish flow; (3) RNFL average and sectoral thickness are greater than control or other pseudopapilledemas. [10,19,20]…”
Section: Discussionmentioning
confidence: 99%